Evaluation and Study of the Cost of Illness of Tuberculosis in Indonesia: A Systematic Review - Hikmah Nova; Yunita Nita; Yuni Priyandani (Journal of Public Health and Pharmacy, 2026)
Introduction: Tuberculosis (TB) remains a significant public health challenge in Indonesia, ranking among the highest global TB burden countries. The financial burden of TB is substantial, encompassing direct medical costs, indirect income losses, and catastrophic household expenditures. Although systematic reviews on TB-related cost-of-illness (COI) have been conducted in various settings, this study aims to fill critical gaps in Indonesian TB financial data, provide comparative regional insights, and offer actionable policy recommendations. Methods: This study used the Systematic Review (SR) method on articles relevant to: COI, disease cost evaluation, or therapy costs for tuberculosis. Articles are examined in English or Indonesian; obtain full text through several search engines such as: PUBMED, Science Direct, Google Scholar, and SCOPUS; research coverage in Indonesia; and in an unlimited time frame. Results: A total of 11 eligible articles were obtained based on inclusion and exclusion criteria. The direct cost of TB-DS ranges from Rp2.2-5.8 million, while TB-MDR reaches Rp190 million. Indirect costs due to loss of revenue reached Rp481.5 million for MDR-TB. Catastrophic costs occurred in 83% of TB-MDR households and 36% of TB-DS, exceeding 20% of annual income. Most patients were men of productive age (18-45 years), with 82.33% losing their jobs during treatment. These findings highlight the need for strategic interventions to reduce the economic impact of TB. Conclusions: The impact of moderate financial burdens and other medical aspects on institutions and individuals is caused by tuberculosis. Further research should be conducted related to this study to obtain a larger estimate.